Healing of buccal dehiscence defects at implants installed immediately into extraction sockets - an experimental study in dogs - Bressan, Eriberto; Sivolella, Stefano; Stellini, Edoardo; Almagro Urrutia, Zoraya; Lang, Niklaus Peter; Botticelli, Daniele (My University, 2013)
Aim: To evaluate the influence of implant positioning into extraction sockets on bone formation at buccal alveolar dehiscence defects. Material and Methods: In six Labrador dogs the pulp tissue of the mesial roots of 4P4 was removed and the root canals were filled. Flaps were elevated bilaterally, the premolars hemi-sectioned and the distal roots removed. The implants were placed in contact with either the buccal (test site) or with the lingual (control site) bony wall of the extraction sockets. Healing abutments were affixed and triangular buccal bony dehiscence defects, about 2.7 mm deep and 3.5 mm wide, were then prepared. No regenerative procedures were done and a non-submerged healing was allowed. After 4 months of healing, block sections of the implant sites were obtained for histological processing and peri-implant tissue assessment. Results: After 4 months of healing, the bony crest and the coronal border of osseointegration at the test sites were located 1.71 ± 1.20 and 2.50 ± 1.21 mm apically to the implant shoulder, respectively. At the control sites, the corresponding values were 0.68 ± 0.63 and 1.69 ± 0.99 mm, respectively. The differences between test and control reached statistical significance (P < 0.05). Residual marginal bone defects were found both at the test and control sites. A statistically significant difference between test and control sites was only found at the lingual aspects (depth 2.09 ± 1.01 and 1.01 ± 0.48 mm, respectively). Similar heights of the buccal biological width were observed at both sites (about 5.1 mm). Conclusions: The placement of implants in a lingual position of the extraction sockets allowed a higher degree of bone formation at buccal alveolar dehiscence defects compared with a buccal positioning. © 2012 John Wiley & Sons A/S.
Keywords: Animal study; Buccal defects; Dehiscence defects; Extraction socket; Hard tissue; Implant dentistry; Osseointegration; Peri-implant mucosa; Soft tissues